URGENSI KUALITAS PRODUK, HARGA DAN KUALITAS PELAYANAN DALAM KEPUTUSAN PEMBELIAN: Studi Pada Produk Rizza Bordir Probolinggo) - Widayanto, Mutinda Teguh; Elly, Moh. Iskak; Prasetyo, Windy (Universitas Islam Syekh-Yusuf, 2021)
This research was conducted to test the urgency of Product Quality, Price and Service Quality in relation to Purchasing Decisions. This research was conducted at Rizza Embroidery, which produces fashion products, which is located in the City of Probolinggo, East Java. The method used in this research is quantitative with a causal associative approach. The population in this study were consumers of Rizza Embroidery in the period August, September and October 2020. Samples were taken using the incidental sampling method developed by Roscoe, and obtained 83 respondents. Multiple Linear Analysis is carried out using the SPSS tool to test the relationship between variables. The results showed that product quality, price and service quality had a significant effect on purchasing decisions either partially or simultaneously. Thus it can be concluded that Product Quality, Price and Service Quality have an urgency to be considered in relation to purchasing decisions.